Efficacy and safety of 12 weeks versus 18 weeks of treatment with grazoprevir (MK-5172) and elbasvir (MK-8742) with or without ribavirin for hepatitis C virus genotype 1 infection in previously untreated patients with cirrhosis and patients with previous null response with or without cirrhosis (C-WORTHY): a randomised, open-label phase 2 trial. Issue 9973 (21st March 2015) - Lawitz, Eric; Gane, Edward; Pearlman, Brian; Tam, Edward; Ghesquiere, Wayne; Guyader, Dominique; Alric, Laurent; Bronowicki, Jean-Pierre; Lester, Laura; Sievert, William; Ghalib, Reem; Balart, Luis; et al.
Summary: Background: There is a high medical need for an interferon-free, all-oral, short-duration therapy for hepatitis C virus (HCV) that is highly effective across diverse patient populations, including patients with cirrhosis or previous null response to pegylated interferon (peginterferon) plus ribavirin (PR-null responders). We aimed to assess the efficacy, safety, and effective treatment duration of grazoprevir (an HCV NS3/4A protease inhibitor) combined with elbasvir (an HCV NS5A inhibitor) with or without ribavirin in patients with HCV genotype 1 infection with baseline characteristics of poor response. Methods: The C-WORTHY trial is a randomised, open-label phase 2 trial of grazoprevir plus elbasvir with or without ribavirin; here we report findings for two cohorts of previously untreated patients with cirrhosis (cohort 1) and those with previous PR-null response with or without cirrhosis (cohort 2) enrolled in part B of the study. Eligible patients were adults aged 18 years or older with chronic HCV genotype 1 infection and HCV RNA concentrations of 10 000 IU/mL or higher in peripheral blood. We randomly assigned patients to receive grazoprevir (100 mg daily) and elbasvir (50 mg daily) with or without ribavirin for 12 or 18 weeks. Randomisation was done centrally with an interactive voice response system; patients and study investigators were masked to treatment duration up to week 12 but not to treatment allocation. The primary endpoint was the proportion of patients achieving HCV RNA less than 25 IU/mL at 12 weeks after end of treatment (SVR12), assessed by COBAS TaqMan version 2.0. This study is registered with ClinicalTrials.gov, number NCT01717326 . Findings: We describe findings for 253 patients enrolled in cohort 1 (n=123) or cohort 2 (n=130). In cohort 1, we randomly assigned 60 patients to the 12-week regimen (31 with ribavirin and 29 with no ribavirin) and 63 to the 18-week regimen (32 with ribavirin and 31 with no ribavirin); in cohort 2, we randomly assigned 65 patients to the 12-week regimen (32 with ribavirin and 33 with no ribavirin) and 65 to the 18-week regimen (33 with ribavirin and 32 with no ribavirin. High SVR12 rates were achieved irrespective of the use of ribavirin or extension of the treatment duration from 12 to 18 weeks; SVR12 rates ranged from 90% (95% CI 74–98; 28/31; cohort 1, 12 weeks, ribavirin-containing) to 100% (95% CI 89–100; 33/33; cohort 2, 18 weeks, ribavirin-containing). Among patients treated for 12 weeks with grazoprevir plus elbasvir without ribavirin, 97% (95% CI 82–100, 28/29) of patients in cohort 1 and 91% (76–98, 30/33) of patients in cohort 2 achieved SVR12. Adverse events reported in more than 10% of patients were fatigue (66 patients, 26% [95% CI 21–32]), headache (58 patients, 23% [95% CI 18–29]), and asthenia (35 patients, 14% [95% CI 10–19]). Interpretation: Treatment with grazoprevir plus elbasvir, both with and without ribavirin and for both 12 and 18 weeks' treatment duration, showed high rates of efficacy in previously untreated patients with cirrhosis and previous PR-null responders with and without cirrhosis. These results support the phase 3 development of grazoprevir plus elbasvir. Funding: Merck & Co, Inc.